Shaping the digital economy 2030: from research to action. Six scenarios - Degryse, Christophe (Brussels, 2017)
"In January 2018 six scenarios on the future of the world of work were published. They have been elaborated by the researchers and experts who participated in the seminar of June 28, 2017, and discussed by the union leaders at the November 2017 seminar "